Discovery and hit-to-lead optimization of 2, 6-diaminopyrimidine inhibitors of interleukin-1 receptor-associated kinase 4. Issue 9 (1st May 2015) - McElroy, William T.; Michael Seganish, W.; Jason Herr, R.; Harding, James; Yang, Jinhai; Yet, Larry; Komanduri, Venukrishnan; Prakash, Koraboina Chandra; Lavey, Brian; Tulshian, Deen; Greenlee, William J.; Sondey, Christopher; et al.
Graphical abstract: Abstract: Interleukin receptor-associated kinase 4 (IRAK4) is a critical element of the Toll-like/interleukin-1 receptor inflammation signaling pathway. A screening campaign identified a novel diaminopyrimidine hit that exhibits weak IRAK4 inhibitory activity and a ligand efficiency of 0.25. Hit-to-lead activities were conducted through independent SAR studies of each of the four pyrimidine substituents. Optimal activity was observed upon removal of the pyrimidine C-4 chloro substituent. The intact C-6 carboribose is required for IRAK4 inhibition. Numerous heteroaryls were tolerated at the C-5 position, with azabenzothiazoles conferring the best activities. Aminoheteroaryls were preferred at the C-2 position. These studies led to the discovery of inhibitors35, 36, and38 that exhibit nanomolar inhibition of IRAK4, improved ligand efficiencies, and modest kinase selectivities.